Effect of concentration of mixed culture of fungi on the biodegradation of palm oil mill effluent - Alade, Abbas O.; Jameel, Ahmed Tariq; Muyibi, Suleyman Aremu; Abdul Karim, Mohamed Ismail; Alam, Md. Zahangir; Ajani, Ayobami O. (2012)
The performance of mixed culture of isolated fungi on the biodegradation of palm oil mill effluent (POME) was evaluated in this study. Specifically, the effect of effect of dosage of the mixed culture on the degradation of lipid content of the POME was investigated in order to determine the suitable incubation for effective biodegradation. The four mixed cultures, (TRQ1/TRQ2, TRQ2/TRQ3, TRQ1/TRQ3 and TRQ1/TRQ2/TRQ3), developed at equal proportions were dosed at 3%, 4% and 6% respectively in a batch process. The percentages removal of the lipid content ranged from 77.4–81.5%, 77.4–81%, and 75.9–82.3%, for 3%, 4% and 6% dosages respectively. The kinetic parameters were evaluated using Zero Order, First Order and Michaelis-Menten expression for biological systems. The fitness of the data indicates ranges of R2 for Zero Order to be 0.46–0.50, 0.40–0.57 and 0.51–0.55, which are less than R2 (0.61–0.69, 0.53–0.70, 0.63–0.76, respectively) obtained for First Order for 3%, 4% and 6% dosages respectively, while R2 obtained for Michaelis-Menten kinetic expression ranged from 0.79–0.94, 0.68–0.87 and 0.69–0.98, respectively. The study shows that the biodegradation of POME was influenced by increasing dosage of inoculums and the biodegradation rate was well fitted to Michaelis-Menten kinetic expression. The incubation period of effective degradation of POME was found to be 5days.